Decreased Foot Sensitivity as a Predictor of Diabetic Foot Ulcers - Wayunah, Wayunah; Nur Aeni, Wiwin; Kuncoro, Martin; Saefulloh, Muhammad (Jurnal Vocational Nursing Sciences (VNUS), 2024)
Introduction: Diabetic foot ulcers are a complication that often occurs in people with diabetes mellitus. This complication begins with a decrease in foot sensitivity which leads to neuropathy, resulting in frequent trauma to the feet. Decreased foot sensitivity in the form of decreased sensation of heat, cold, and pain is a dangerous complaint because it has a very high risk of causing foot ulcers or neuropathic foot ulcers. Objective: This study aimed to determine the relationship between the level of foot sensitivity and the incidence of dibetic foot ulcers in diabetes mellitus patients. Method: The type of research is a descriptive correlation with a cross-sectional approach. The population, all DM pstients at Internal Medicine Clinic 1 and 2 Indramayu District Hospital. The sample was 48 people taken by accidental sampling. Data collection tools used observation sheets and 10 G monofilament, while data analysis techniques used the Chi-square test. Result: The research results obtained from 44 respondents showed that 22 respondents (%) experienced neuropathy. Of these, 21 (95.5%) had ulcers. Meanwhile, of the 26 respondents who did not have neuropathy, 21 (80.8%) did not have ulcers. The results of further analysis obtained a p-value of 0.000 and an OR value of 88.2. Conclusion: The conclusion from this study is that there is a relationship between the level of sensitivity and the incidence of diabetic foot ulcers. DM patients who experience neuropathy are 88.2 times more likely to develop ulcers than those who do not experience neuropathy. Suggestions are given to nurses to continue making efforts to prevent diabetic foot ulcers by checking the sensitivity of the patient's feet regularly, at least once a year.